Descriptive logic using in Web-service problems - Zakharova, O.V. (Інститут програмних систем НАН України, 2017)
Currently, Web services allow us to solve specific business problems that implement business processes in various fields of human activity. But in order to get an executable Web service, we have to be able to efficiently solve many Web services’ problems at all stages of their life cycle. Descriptive logics, due to their reasoning mechanisms and capabilities of logical inference and semantic descriptions, are an effective and powerful tool for solving Web services problems. The purpose of this work is to establish a chain of Web services’ tasks at the functional level and define approaches to their solution using the mechanisms of descriptive logics.